Faktor-faktor yang memengaruhi minat investasi pada pasar modal - Vica Nastasia Tokii; Sri Zaniarti (Vikara: Student Academic Journal of Business and Management, 2025)
The pandemic, that has hit Indonesia, has significantly changed people's activities, forcing them to stay at home. This has created a new trend of creating content on social media, such as TikTok, YouTube, and Instagram, which is mostly about sharing knowledge. These activities on social media can make someone popular and gain many followers, thus earning them the title of social media influencer. One of the types of information shared is education about the capital market. This study aims to analyse the influence of investment knowledge and social media influencers on students' interest in investing. The objective of this research is to examine the relationship between investment knowledge and social media influencers on students' interest in investing. The research method used multiple analysis processed using SPSS. The sampling technique in this study used simple random sampling, with a sample size of 152 respondents. The findings of this study partially indicate that investment knowledge does not influence investment intentions, while social media influencers do influence investment intentions. This shows that the influence of others, especially information obtained from social media such as influencers, greatly influences a person's decision to invest.